Metabolites of 2,3-diketogulonate delay peroxidase action and induce non-enzymic H(2)O(2) generation: Potential roles in the plant cell wall - Kärkönen, Anna (Arch Biochem Biophys, 2017)
A proportion of the plant's l-ascorbate (vitamin C) occurs in the apoplast, where it and its metabolites may act as pro-oxidants and anti-oxidants. One ascorbate metabolite is 2,3-diketogulonate (DKG), preparations of which can non-enzymically generate H(2)O(2) and delay peroxidase action on aromatic substrates. As DKG itself generates several by-products, we characterised these and their ability to generate H(2)O(2) and delay peroxidase action. DKG preparations rapidly produced a by-product, compound (1), with λ(max) 271 and 251 nm at neutral and acidic pH respectively. On HPLC, (1) co-eluted with the major H(2)O(2)-generating and peroxidase-delaying principle. Compound (1) was slowly destroyed by ascorbate oxidase, and was less stable at pH 6 than at pH 1. Electrophoresis of an HPLC-enriched preparation of (1) suggested a strongly acidic (pK(a) ≈ 2.3) compound. Mass spectrometry suggested that un-ionised (1) has the formula C(6)H(6)O(5), i.e. it is a reduction product of DKG (C(6)H(8)O(7)). In conclusion, compound (1) is the major H(2)O(2)-generating, peroxidase-delaying principle formed non-enzymically from DKG in the pathway ascorbate → dehydroascorbic acid → DKG → (1). We hypothesise that (1) generates apoplastic H(2)O(2) (and consequently hydroxyl radicals) and delays cell-wall crosslinking — both these effects favouring wall loosening, and possibly playing a role in pathogen defence.